A comparative analysis of consensus protocols for dealing power theft issue in Pakistan. Issue 7 (3rd October 2021) - Maqbool, Ayesha; Sattar, Sumera; Naheed, Amna; Khalid, Sana; Rana, Tauseef; Afzal, Farkhanda; Cancan, Murat
Abstract: Power is considered as a boon for life, lifeline of a country's economy; a key instrument for the socio-economic evolution of any country. Pakistan faces the issue of power theft that worsens the economy of utilities. The purpose of research is to modernize Pakistan's power sector with the usage of Blockchain. Research is based on a comparative analysis of proof of stake (POS) and proof of authority (POA) consensus protocols for the power theft issue for small, medium, or large scales of consumers; results showing automated and pre-selected processing time of transactions running on different nodes of POS and POA along. By comparative analysis of POS and POA; it is shown that the performance of Blockchain remains unaffected by the consensus protocol. To further strengthen the findings the statistical analysis data is carried out to establish the uniqueness of sampled data. The result establishes that Blockchain performs equally well for different architectures of the proposed architecture. The consensus protocol helps in achieving a suitable governing style with no effect on Blockchain performance.